Identification of the variability of a common bean collection through morphological, physiological, biochemical, and molecular relationships (2014)
The present study was carried out in Corpoica, C.I. Tibaitata (Mosquera, Colombia) at an altitude of 2,540 m a.s.l. in six environments composed of different seasons and at an altitude of 1,485 m a.s.l. in the International Center of Tropical Agriculture (CIAT), Calima, Colombia. Morphological, physiological, biochemical, and molecular descriptors were used to estimate the genetic variability between 36 Colombian bean accessions, of which four were wild and the others cultivated. Diacol Calima (Nueva Granada from the Andean gene pool) and ICA Pijao (Mesoamerican from the mesoamerican gene pool) were used as controls. The combined analysis of the qualitative and quantitative variables was carried out with Gower distance and an unified data matrix with 315 descriptors. The relationships between the genetic distances differentiated the bean collection into two genetic groups: Andean and Mesoamerican. The following groups of characteristics presented high association: total morphology with qualitative morphology (P=0.91), physiological evaluation with grouped evaluation of morphological, quantitative, and physiological characteristics (P=0.91), characterization of isoenzymatic and molecular markers with respect to just molecular markers (P=0.99) and the characterization of all the studied markers in relation to the molecular and isoenzymatic markers (P=0.88).